Optimalisasi Pemberdayaan Usaha 'Jamu Coro Mba Ida' sebagai Perwujudan UMKM Go Digital di Desa Temuroso - M. Burhan Rubai Wijaya; Morinda Salwa Oktriana; Nawang Wulan Sari; Lutfiyah Aprilliana; Anggita Sonyaruri (Jurnal Bina Desa, 2026)
This research discusses devotion through empowerment and mentoring activities for superior MSMEs in Temuroso Village, Demak Regency, namely Mba Ida's Jamu Coro business using digital technology in accordance with current developments. The purpose of the following research is to encourage the creation of sustainable village development with the presence of increasing MSMEs going digital while also being able to encourage an increase in the economy of the community in the village. This research was written using the Participatory Action Research Method which consists of 3 stages, namely problem identification, action planning, implementation, to evaluation and reflection. Some of the results of this discussion are (1) mentoring and digital marketing training for MSME actors; (2) increasing the branding of Mba Ida's Jamu Coro product; (3) creating a Google Maps location point for the place of business; (4) procuring Instagram social media accounts and content; and (5) creating a business name banner. The creation of this article is expected to support the improvement of local MSMEs so that they are able to compete while being able to maintain the sustainability of cultural products in Indonesia.